2011
DOI: 10.1155/2011/623168
|View full text |Cite
|
Sign up to set email alerts
|

Yoga for Persistent Fatigue in Breast Cancer Survivors: Results of a Pilot Study

Abstract: Approximately one-third of breast cancer survivors experiences persistent fatigue for months or years after successful treatment completion. There is a lack of evidence-based treatments for cancer-related fatigue, particularly among cancer survivors. This single-arm pilot study evaluated the feasibility and preliminary efficacy of a yoga intervention for fatigued breast cancer survivors based on the Iyengar tradition. Iyengar yoga prescribes specific poses for individuals with specific medical problems and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
43
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 70 publications
2
43
1
Order By: Relevance
“…In Iyengar yoga, emphasis is placed on awareness and precision of body alignment during postures, often with the aid of props. Iyengar yoga has been tested as a therapeutic treatment with beneficial results for various conditions, including depressed mood and anxiety (Balasubramaniam, Telles, & Doraiswamy, 2013;Javnbakht, Hejazi Kenari, & Ghasemi, 2009;Michalsen et al, 2005;Shapiro & Cline, 2004;Shapiro et al, 2007;Woolery, Myers, Sternlieb, & Zeltzer, 2004), persistent fatigue (Bower, Garet, & Sternlieb, 2011), and pain conditions including low back pain , osteoarthritis (Bukowski, Conway, Glentz, Kurland, & Galantino, 2006;Garfinkel, Schumacher, Husain, Levy, & Reshetar, 1994;Kolasinski et al, 2005), rheumatoid arthritis (Evans et al, 2013), chronic pancreatitis (Sareen, Kumari, Gajebasia, & Gajebasia, 2007), and carpal tunnel syndrome (Garfinkel et al, 1998). Studies of Iyengar yoga for IBS have been favorable, providing a decrease in symptomatology and anxiety (Evans et al, 2014;Kuttner et al, 2006;Taneja et al, 2004).…”
mentioning
confidence: 99%
“…In Iyengar yoga, emphasis is placed on awareness and precision of body alignment during postures, often with the aid of props. Iyengar yoga has been tested as a therapeutic treatment with beneficial results for various conditions, including depressed mood and anxiety (Balasubramaniam, Telles, & Doraiswamy, 2013;Javnbakht, Hejazi Kenari, & Ghasemi, 2009;Michalsen et al, 2005;Shapiro & Cline, 2004;Shapiro et al, 2007;Woolery, Myers, Sternlieb, & Zeltzer, 2004), persistent fatigue (Bower, Garet, & Sternlieb, 2011), and pain conditions including low back pain , osteoarthritis (Bukowski, Conway, Glentz, Kurland, & Galantino, 2006;Garfinkel, Schumacher, Husain, Levy, & Reshetar, 1994;Kolasinski et al, 2005), rheumatoid arthritis (Evans et al, 2013), chronic pancreatitis (Sareen, Kumari, Gajebasia, & Gajebasia, 2007), and carpal tunnel syndrome (Garfinkel et al, 1998). Studies of Iyengar yoga for IBS have been favorable, providing a decrease in symptomatology and anxiety (Evans et al, 2014;Kuttner et al, 2006;Taneja et al, 2004).…”
mentioning
confidence: 99%
“…Yoga interventions have also demonstrated positive effects on behavioural symptoms related to fatigue, including depressed mood, pain, and physical function. Julienne E. Bower evaluated the acceptability of an Iyengar yoga intervention for fatigued breast cancer survivors which have shown to be well-suited in cancer patients [43].…”
Section: Role Of Physiotherapy In Cancer Related Fatiguementioning
confidence: 99%
“…Despite yoga being an integral part of Indian culture, clinical research into using yoga as treatment modality has been initiated only in the last few decades. Findings in recent studies have been encouraging for using yogabased interventions in pain disorders (Bower, Garet, & Sternlieb, 2011;Carson, Carson, Jones, Bennett, Wright, & Mist, 2010;Cramer, Lauche, Langhorst, Dobos, & Michalsen 2014;Do Ros ario, Orcesi, Kobayashi, Aun, & Diolindo Assumpção, 2013;Lee, Moon, & Kim, 2014;Nambi, Inbasekaran, Khuman, Devi, & Shanmugananth, 2014;Rudrud, 2012;Sharan, Manjula, Urmi, & Ajeesh, 2014). Studies have demonstrated therapeutic effects of yoga in chronic pain conditions such as low back ache, headache, fibromyalgia, and chronic fatigue syndrome (Bhatia, Dureja, Tripathi, Bhattacharjee, Bijlani, & Mathur, 2007;Holtzman & Beggs, 2013;Lauche, Cramer, H€ auser, Dobos, & Langhorst, 2015;Oka, Tanahashi, Chijiwa, Lkhagvasuren, Sudo, & Oka, 2014).…”
Section: Introductionmentioning
confidence: 99%